2006
DOI: 10.1103/physrevlett.97.206803
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Surface, Bulk, and Space-Charge-Layer Conductivity inSi(111)(7×7)

Abstract: A novel approach for extracting genuine surface conductivities is presented and illustrated using the unresolved example of Si(111)-(7 x 7). Its temperature-dependent conductivity was measured with a microscopic four point probe between room temperature and 100 K. At room temperature the measured conductance corresponds to that expected from the bulk doping level. However, as the temperatures is lowered below approximately 200 K, the conductance decreases by several orders of magnitude in a small temperature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 20 publications
4
57
0
Order By: Relevance
“…The four-point resistance is related to the resistivity by R 4pp,bulk = / ͑2 s͒. 4 Using this relationship, our measured values corresponds to a resistivity of 120Ϯ 20 ⍀ cm, which is consistent with the accepted bulk resistivity of 130 ⍀ cm. 14 Thus, it can be inferred that the measurements are bulk sensitive-which, in turn, indicates that the surface resistivity must be greater than approximately 10 ⍀ ͑otherwise the surface resistivity would dominate the measurement͒.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…The four-point resistance is related to the resistivity by R 4pp,bulk = / ͑2 s͒. 4 Using this relationship, our measured values corresponds to a resistivity of 120Ϯ 20 ⍀ cm, which is consistent with the accepted bulk resistivity of 130 ⍀ cm. 14 Thus, it can be inferred that the measurements are bulk sensitive-which, in turn, indicates that the surface resistivity must be greater than approximately 10 ⍀ ͑otherwise the surface resistivity would dominate the measurement͒.…”
supporting
confidence: 60%
“…Four-point probes have been scaled down to sizes of a few micrometers 2 and applied for investigations on a wide range of materials. [3][4][5] The standard microscopic four-point probe, which consists of four individual Au-coated SiO 2 cantilevers, cannot meet the recent demands of the semiconductor industry for small pitched complementary metal-oxide-semiconductor ͑CMOS͒ compatible probes. In order to meet the criteria of CMOS compatibility, the probes cannot contain metals or silicides with high mobility, since such materials could greatly affect the properties of the investigated samples.…”
mentioning
confidence: 99%
“…Measurements on bulk semiconductors are dominated by other parallel conduction channels, including bulk conduction and conduction through the space charge region, as the surface conductance is typically several orders of magnitude smaller. Microscopic probes, such as the scanning tunneling microscope [25][26][27] and microscopic cantilevers 28,29 , have been utilized to make surface conductance measurements, but only one study uses thin sheets of Si 30 , as found in SOI. Because of a reduced penetration of electric field into the bulk, the use of smaller probe spacings maximizes the surface contribution to charge transport in measurements on bulk samples.…”
Section: Discussionmentioning
confidence: 99%
“…We take ln(l/d) ≈ 10 which corresponds to d = 1 − 1000 nm within 30% accuracy. The measured conductivity contains the contributions of the conduction through the topmost layer of the Si(111)-7 × 7 surface, as well as through the bulk and the sub-surface layer [11,16,17]. The sub-surface layer is known to be a depletion layer due to the Fermi-level pinning by surface state.…”
Section: Methodsmentioning
confidence: 99%